2001
DOI: 10.1007/s11746-001-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on recrystallization behavior of cocoa butter

Abstract: Crystallization of cocoa butter in the β phase directly from the melt is only possible by employing the memory effect of cocoa butter. Cocoa butter crystallized in the β phase, heated to the so-called maximal temperature (just above its melting end point), recrystallizes in the β phase after cooling to a crystallization temperature. The influence of the maximal and crystallization temperatures on the recrystallization behavior has been investigated for two cocoa butters. Rapid-starting recrystallization into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 12 publications
(20 reference statements)
2
39
0
1
Order By: Relevance
“…Form bV is a relatively stable form found after appropriate cooling of a melted chocolate with shelf life often more than one year, but this depends on numerous (sometimes unknown) parameters [20]. The most stable form (bVI) cannot be produced directly from the melted chocolate (except by the addition of bVI CB seeds and under very well controlled conditions [21,22].…”
Section: Polymorphismmentioning
confidence: 99%
“…Form bV is a relatively stable form found after appropriate cooling of a melted chocolate with shelf life often more than one year, but this depends on numerous (sometimes unknown) parameters [20]. The most stable form (bVI) cannot be produced directly from the melted chocolate (except by the addition of bVI CB seeds and under very well controlled conditions [21,22].…”
Section: Polymorphismmentioning
confidence: 99%
“…The liquid CB was then placed in a precooled water bath (Fisher Scientific Isotemp 3006D) at 23°C to induce recrystallization of CB utilizing the crystal memory effect (van Malssen et al 1996;Langevelde et al 2001). Van Malssen found that crystallization of cocoa butter directly from the melt into β polymorphs is not possible.…”
Section: Cocoa Butter Seed Preparationmentioning
confidence: 99%
“…A complex mixture of TAGs in natural products creates a variety of polymorphic forms as a function of temperature [1,2]. The study of pure TAGs is an effective way to understand structural transformations taking place in natural fat products.…”
Section: Introductionmentioning
confidence: 99%